Trademark and unfair competition conflicts : historical-comparative, doctrinal, and economic perspectives - Dornis, Tim W. (Cambridge intellectual property and information law, 2017)
"Both in Europe and the United States, a socioeconomic cataclysm of industrialization and market liberalization-including the invention of branding, mass advertising, and marketing psychology-was the driving force behind the construction of modern trademark and unfair competition laws. During the last two centuries, legal doctrine accordingly underwent partly groundbreaking transformations. Many of these account for today's transatlantic dichotomy, particularly in the field of trademark and unfair competition choice of law, or conflicts law. My analysis will focus on the most relevant characteristics of legal doctrine between the eighteenth and twenty-first centuries. I argue that a closer look at conceptual and structural differences, as well as commonalities between European and US law, provides the basis for a reconceptualization of the field"--